Numerical modeling of horizontal stratified two-phase flows using the AIAD model - Yan, Hongjie; Zhang, Huimin; Höhne, Thomas; Liao, Yixiang; Lucas, Dirk; Liu, Liu (Frontiers in Energy Research, 2022)
In nuclear reactor safety research, the countercurrent gas-liquid two-phase flow in the hot leg of a pressurized water reactor (PWR) has attracted considerable attention. Previous work has proven that the algebraic interfacial area density (AIAD) model implemented in ANSYS CFX can effectively capture the gas-liquid interface and avoid the loss of information regarding the interfacial structure, which occurs after phase averaging in the Euler–Euler two-fluid approach. To verify the accuracy of the AIAD module implementation in ANSYS Fluent, the model based on the experimental data from the WENKA facility is validated in this work. The effects of the subgrid wave turbulence model, turbulence damping model, and droplet entrainment model are simultaneously investigated, which have been shown to be important in the previous work with CFX. The results show that the simulations are considerably and significantly deviate from the experiments when the turbulence damping is not considered. The free surface modeling of two-phase flow can be optimized by using the droplet entrainment model. The consistency between the simulation and experimental results is not enhanced after the subgrid wave turbulence model is adopted. Further investigations regarding the implementation of the subgrid wave turbulence model are necessary.